Via Media:: The Circulation of Narratives and their Influence on Tourists’ and Residents’ Actions and Memories - Toxey, Anne (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract This article illustrates the interplay of the local and global in the circulation of narratives that shape and inform memories of a place while also responding to and impacting its material culture. Tracing narratives of residents’ and tourists’ interpretations of an ancient, Italian cave-city (the Sassi of Matera) through media and action, the study shows how different groups engage the malleability of memory and site representation to reinforce identity constructions and political-economic goals.